2016
DOI: 10.1002/hbm.23399
|View full text |Cite
|
Sign up to set email alerts
|

Active delineation of Meyer's loop using oriented priors through MAGNEtic tractography (MAGNET)

Abstract: Streamline tractography algorithms infer connectivity from diffusion MRI (dMRI) by following diffusion directions which are similarly aligned between neighbouring voxels. However, not all white matter (WM) fascicles are organized in this manner. For example, Meyer’s loop is a highly curved portion of the optic radiation (OR) that exhibits a narrow turn, kissing and crossing pathways, and changes in fascicle dispersion. From a neurosurgical perspective, damage to Meyer’s loop carries a potential risk of inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 106 publications
(182 reference statements)
0
56
0
Order By: Relevance
“…While this approach makes perfect sense in a true crossing configuration, in the case of kissing fibers or a sharp bend it will potentially result in both false-positive and false-negative trajectories. 110 Matters become even more complicated in the case of fanning fiber configurations, as one should also take into account the polarity of the fanning. For example, fibers typically diverge as they move towards the cortex, but they converge when tracking in the opposite direction.…”
Section: Proper Treatment Of Ambiguous Local Geometriesmentioning
confidence: 99%
“…While this approach makes perfect sense in a true crossing configuration, in the case of kissing fibers or a sharp bend it will potentially result in both false-positive and false-negative trajectories. 110 Matters become even more complicated in the case of fanning fiber configurations, as one should also take into account the polarity of the fanning. For example, fibers typically diverge as they move towards the cortex, but they converge when tracking in the opposite direction.…”
Section: Proper Treatment Of Ambiguous Local Geometriesmentioning
confidence: 99%
“…Another approach proposed by Benjamin et al (2014) is to place different ROIs around the LGN and within the sagittal stratum, or by seeding from the optic chiasm ( Kammen et al, 2016 ). A recent study suggested using seeding around the Meyer's loop with an a-priori fiber orientation ( Chamberland et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean ML-TP distances for both brain hemispheres, measured to be 30.0 ± 4.5 mm for the healthy volunteer group and 30.9 ± 2.4 mm for the patient group (pre-operatively), are within the range of the ML-TP distance reported on by Ebeling et al (1988) and outcomes from other OR reconstruction methodologies. For example, ConTrack ( Sherbondy et al, 2008 ) showing 28 ± 3.0 mm, Streamlines Tracer technique (STT) showing 37 ± 2.5 mm ( Yamamoto et al, 2005 ) and 44 ± 4.9 mm ( Nilsson et al, 2007 ), Probability Index of Connectivity (PICo) showing 36.2 ± 0.7 mm ( Dayan et al, 2015 ), tractography on Human Connective Project (HCP) multi-shell data showing 30.7 ± 4.0 mm ( Kammen et al, 2016 ), and MAGNET showing 36.0 ± 3.8 mm ( Chamberland et al, 2017 ). It appeared, furthermore, that the mean ML-TP for both the healthy volunteers and the patients was larger in the left hemisphere compared to the right hemisphere, which is not consistent with a recent study by James et al (2015) that indicated a significantly higher ML-TP in the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Additional regions of interest to exclude artifactual contributions were extracted from the Freesurfer parcelation, namely the contralateral gray matter mask. Finally sagittal, axial and coronal ROIs were drawn for each individual subject in order to exclude lateral projections from the acoustic radiation, posterior projections of the corpus callosum, parts of the cingulum bundle and brainstem (Dayan et al, 2015a,b;Kammen et al, 2016;Nowell et al, 2016;Chamberland et al, 2017). These regions were used to perform tractography with a probabilistic algorithm in MRTrix3 with 2nd order integration over the fiber orientation distribution [iFOD2 (Tournier et al, 2010)] with a 90 • angular threshold, 5000 selected streamlines and FA and FOD amplitude threshold of 0.15 and 0.1, respectively.…”
Section: Tractography Reconstructionsmentioning
confidence: 99%
“…The anterior bundle, most often denominated Meyer's Loop, is most at risk in the types of resections described above, and the correlation between the extent of its resection and resulting visual field deficits following surgery in adults is well established (Falconer and Wilson, 1958). Diffusion MRI allows extraction of measures that identify the main directions of water molecular displacement and from that a three-dimensional trajectory of fiber bundles can be reconstructed [tractography (Conturo et al, 1999) and has been used in numerous studies to reconstruct the optic radiations (Yogarajah et al, 2009;Clatworthy et al, 2010;Martínez-Heras et al, 2015;Chamberland et al, 2017)]. Despite the success of tractography in demonstrating involvement of the optic radiations in the resected tissue and subsequent correlation between the extent of optic radiation involvement and postsurgical visual fields in adults (Yam et al, 2010;Winston et al, 2011Winston et al, , 2012Winston et al, , 2014a, there is very little literature on the use of the technique in pediatric series.…”
Section: Introductionmentioning
confidence: 99%